The Effectiveness of Group Counseling with Self-instruction and Cognitive Restructuring Techniques to Improve Hardiness - Khoiriyah, Zaenatul; Puji Sugiharto, Dwi Yuwono; Japar, Muhammad (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2020)
When completing final project, students are faced with many obstacles, such as confusion in determining the topic and difficulties in finding lecturers. Hardiness has an important role to persistently manage and overcome the obstacles. Thus, this study aimed to test the effectiveness of group counseling with self-instruction and cognitive restructuring techniques to improve hardiness of students who were completing their final projects majoring in Islamic Guidance and Counseling program in IAIN Kudus. This study used pretest-posttest control group design involving 21 students selected using purposive sampling. To collect the data, this study used hardiness scale. The results of Wilcoxon test showed that self-instruction technique effectively improved students’ hardiness of (Z= -2.201, P< 0.05) as well as cognitive restructuring technique effectively improved students’ hardiness of (Z= -2.371, P< 0.05). Regarding this findings, both techniques are suggested to be independently applied to improve students’ hardiness.